Offers of compromises and schemes of arrangements in South African company law - Kralik, Florian (Department of Commercial Law, 2023)
There are many different reasons why people want to acquire companies. Although takeovers are an extremely dangerous and high risk game, they are becoming more and more numerous in the modern business world. An acquiror, however, tries to minimize his risk by trying to take over a company with a scheme of arrangement applying section 311 of the South African Companies Act, which gives him the necessary tool to takeover a 'clean' company without unknown creditors. That means that such a scheme must be a compromise or arrangement 'between the company and its creditors' before it can be sanctioned by court and therefore becomes binding on all the creditors, whether they are known or unknown. At least 3/4 of the creditors votes and numbers must support the arrangement. To draft a scheme for this reason alone, however, would not be a big problem. What makes these takeovers so sophisticated is that every acquiror also wants to profit from the assessed loss of the target company, which is often available. Therefore to draft a scheme, which, on the one hand complies with section 311 of the Companies Act, and on the other hand, does not comply with section 20 (1) (a) (ii) of the Income Tax Act in order to profit from the assessed loss, makes the scheme industry difficult.